Robust classification of single-cell transcriptome data by nonnegative matrix factorization - Shao, Chunxuan; Höfer, Thomas (Bioinformatics, 2017)
AbstractMotivation. Single-cell transcriptome data provide unprecedented resolution to study heterogeneity in cell populations and present a challenge for unsu
Advance access publication date: 23 September 2016
Gesehen am 27.07.2018